2019
DOI: 10.3126/jgmcn.v12i1.22607
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Hypertensive Retinopathy in a Tertiary Centre in Western Nepal

Abstract: Objective: The present study was done to find out prevalence of hypertensive retinopathy among patients attending in OPD in GMC. Methods:A hospital based cross-sectional study was performed among 200 hypertensive patients visiting eye OPD from Dec 2016 to Dec 2017. Detailed eye examination including fundus evaluation under mydriasis was done on all subjects and hypertensive retinopathy was graded according to Keith, Wagner and Barker classification by ophthalmologist using 90 dioptre lens. Patient having diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…For instance, Godar ST et al 21 reported higher proportions of grade 1 (7.36%) and grade 2 (17.86%) compared to grade 3 (10.52%) and grade 4 (3.15%). Similar patterns were noted by Ray S et al, 25 Cholera P et al, 18 and Pun CB et al 26 in their respective studies. Additionally, Ifrath Nusaiba et al 19 reported that the highest number of hypertensive retinopathy patients had grade 1 (32), followed by grade 2 (16), with fewer cases of grade 3 and 4 (8 and 1, respectively).…”
Section: Discussionsupporting
confidence: 85%
“…For instance, Godar ST et al 21 reported higher proportions of grade 1 (7.36%) and grade 2 (17.86%) compared to grade 3 (10.52%) and grade 4 (3.15%). Similar patterns were noted by Ray S et al, 25 Cholera P et al, 18 and Pun CB et al 26 in their respective studies. Additionally, Ifrath Nusaiba et al 19 reported that the highest number of hypertensive retinopathy patients had grade 1 (32), followed by grade 2 (16), with fewer cases of grade 3 and 4 (8 and 1, respectively).…”
Section: Discussionsupporting
confidence: 85%
“…31%. (However, in this study, Modified Keith-Wagner-Barker Classification was used as reference) 10. In a study conducted by Adhikari et al most of the patients with HR had Grade II HR i.e.…”
mentioning
confidence: 98%